Food consumption patterns and score among women receiving cash assistance: emergency nutrition response in drought affected pastoralist community eastern Ethiopia - Aboma Motuma; Mohammed Jemal Dawe; Assefa Tola Gemada; Temam Beshir; Behailu Hawulte; Hamdi Fekredin Zakaria; Kedir Teji Roba (Journal of Health, Population and Nutrition)
Abstract Background Food insecurity remain sub-Saharan African issues, particularly pastoral society. Pastoralist women’s active role in the household economy and livelihood diversification despite their marginal position in terms of access to basic health and education services, and decision making. The use of cash transfers in humanitarian settings is an emerging; however, there is scare of evidence on how well cash transfers improve nutritional outcomes. Moreover, evidence limited on food consumption scores, particularly pastoralist women in Ethiopia. Therefore, this study aims to assess food consumption score and associated factors among cash-beneficiary women in emergency nutrition response in drought-affected pastoralist communities in Eastern Ethiopia. Method A community-based cross-sectional study design was conducted among cash-beneficiary women in 2022. Data was collected using a pretested structured questionnaire among 374 randomly selected cash beneficiary women. Food consumption score was calculated using a seven-day dietary recall of food items consumed. After collecting the data the food items were categorized into eight food groups and summed up. EPI Data version 3.1 software was used to code, enter, and clean the data. SPSS version 23 was used for analysis. The study used ordinal logistic regression to identify factors influencing the food consumption score. Variables with p-value < 0.25 in bivariable analysis were considered for multivariable analysis, and 95% confidence interval was used to measure the strengths of association at p-values < 0.05. Results The study shows that the acceptable food consumption score among cash beneficiaries’ women was 43.3% (95% CI 38.27–48.36%). The source of food from own product (AOR = 2.18, [95% CI: 1.68, 4.56]), and animal source food (AOR = 12.14, [95% CI: 5.25, 28.0.6]) were significantly associated with the acceptable food consumption score. However, the acceptable food consumption score was significantly lower among cash-beneficiary women who requested by kebeles administrative to share money for registration (AOR = 0.059, [95% CI: 0.011, 0.32]). Conclusion The findings show that the acceptable food consumption score was low among cash-beneficiary women. The government should be maximizing on local food production and animal-sourced food to scale up the acceptable food consumption score. Policies and programs should be enhancing and promoting on sustainable local food products. Moreover, strengthening the policies that promote the welfare of pastoralist women, providing training on women's capacity building, enhancing women's empowerment, and encouraging their participation in the decision-making process are essential to mitigating the problems pastoralist women face.